Beeinflussung der Fließeigenschaften von Lasersinterpulver mittels Fließhilfsmitteln - Man, Yunhao

Wärmebehandlung von Polymeren zum Modifizieren von Materialeigenschaften für das Selektive Lasersintern - Seuthe, Jan

Fließfähigkeit von Schüttgütern bei erhöhten Temperaturen (Studienarbeit) - Ewe, Frederik

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Jubilate (08.05.2022): 1. Mose 1,1-4a.26-28.31a; 2, 1-4a - Janus, Richard (Er ist unser Friede. Lesepredigten 1. Advent 2021 bis Pfingstmontag 2022. Textreihe IV/1)

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th on Knowledge Capture Conference)

Examining the role of stress and information security policy design in information security compliance behaviour: An experimental study of in-task behaviour - Trang, Simon Thanh-Nam; Nastjuk, I. (Computers & Security)

The perils of gamification: Does engaging with gamified services increase users’ willingness to disclose personal information? - Trang, Simon Thanh-Nam; Weiger, W. (Computers in Human Behavior)

Corona Tracing Apps – Eine Analyse und Strukturierung des europäischen Marktes - Brendel, A.B.; Greve, M.; Masuch, K.; Trang, Simon Thanh-Nam (HMD Praxis der Wirtschaftsinformatik)

Unsupervised Relation Extraction Using Sentence Encoding - Manzoor, Ali; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2021 Satellite Events)

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

On the Limited Impact of Visualizing Encryption: Perceptions of E2E Messaging Security - Stransky, Christian; Wermke, Dominik; Schrader, Johanna; Huaman, Nicolas; Acar, Yasemin; Fehlhaber, Anna Lena; Wei, Miranda; Ur, Blase; Fahl, Sascha (Seventeenth Symposium on Usable Privacy and Security, SOUPS 2021, August 8-10, 2021)

They Would do Better if They Worked Together: The Case of Interaction Problems Between Password Managers and Websites - Huaman, Nicolas; Amft, Sabrina; Oltrogge, Marten; Acar, Yasemin; Fahl, Sascha (2021 IEEE Symposium on Security and Privacy (SP))

"It’s the Company, the Government, You and I": User Perceptions of Responsibility for Smart Home Privacy and Security - Haney, Julie M.; Acar, Yasemin; Furman, Susanne (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Investigating Web Service Account Remediation Advice - Neil, Lorenzo; Bouma-Sims, Elijah; Lafontaine, Evan; Acar, Yasemin; Reaves, Bradley (Seventeenth Symposium on Usable Privacy and Security, SOUPS 2021, August 8-10, 2021)

Human Factors in Secure Software Development - Acar, Yasemin

Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.